Struktur Organisasi dan Efektivitas Operasional Hotel Berbintang 5: Hubungan, Dampak, dan Implikasinya Terhadap Kinerja Hotel (International Forum of Researchers and Lecturers, 2025)
Organizational structure plays a crucial role in enhancing the operational effectiveness of an organization or company. In the context of a five-star hotel, a clear and appropriate organizational structure helps improve coordination between departments, clarifies employees' roles and responsibilities, and optimizes operational processes. This study aims to determine the extent of the influence of organizational structure on operational effectiveness in five-star hotels. The research method employed is quantitative, using simple linear regression analysis. The findings indicate that organizational structure has a significant impact on the operational effectiveness of hotel employees. Specifically, the organizational structure, along with the work environment and shared motivation, contributes to 73% of the impact on employee performance.